Empowering Youth for Social Change: The Role of Social Entrepreneurship Education - Ramasamy, James; Moripi, Fransiscus B.; Chan, Kevin (Aurora: Journal of Emerging Business Paradigms, 2024)
Empowering youth to drive social change is imperative for building sustainable communities and addressing pressing societal challenges. Social entrepreneurship education emerges as a critical tool in fostering the necessary skills, mindset, and resources among young individuals. This research article examines the pivotal role of social entrepreneurship education in empowering youth for social change. Through a comprehensive review of existing literature and case studies, this study explores the significance of integrating social entrepreneurship education into youth development programs and formal education systems. Furthermore, it investigates the impact of such education on enhancing youths' capacity to identify social issues, develop innovative solutions, and implement sustainable ventures. The article also discusses the challenges and opportunities associated with implementing social entrepreneurship education initiatives, along with recommendations for policymakers, educators, and practitioners to effectively empower youth for meaningful social impact.